Vpliv izobraževanja o depresiji na odnos zdravnikov splošne medicine do obravnave depresivnih bolnikov - Bilban, Marjan (Zdravstveno varstvo, 2003)
Around 60 percent of depressed persons attend surgeries of general practitioners. Physicians are much better trained in recognizing and evaluating physical disorders than mental ones. The aim of our study is to stress the role of appropriate psychiatric knowledge and professional skills that should make general practitioners better equipped for entry into the patient's psychosocial world and, as we assume in our study, help them recognize and treat depressions. The Department of Psychiatry organised a two-day seminar on depression for general practitioners with the aim of deepening their knowledge on this mental disorder. The seminar was attended by30 general practitioners; half of them were specialists and the remainder were medical graduates. Twenty-six of them filled in a pre-seminar and a post-seminar questionnaire about treatment modalities, work capacity evaluation, etc. The majority of respondents came across depressed patients fairly frequently. Most of those polled viewed depression as an illness for which patients need comprehensive treatment and human support and encouragement; work capacity assessment was reported to be mostly based on the severity of the illness, i.e the patient's mental state at the time of examination; anti-depressant medicines and psychotherapy were the most common treatment modalities; and loneliness was considered the major triggering factor for depression. As a result of improved physicians' knowledge and perceptions about depression the post-training responses differed to a considerable extent from those obtained before the seminar. A considerable shift in the assessment of depression treatment efficiency was noticed. A much greater emphasis was given to the need to outline possible solutions to problems, and to help patients to accept and manifest their feelings, rather than just take advice and accept solutions from the physician. Thanks to a more profound knowledge of depression management, the work of general practitioners with depressed patients will be more successful and more effective.
Keywords: depresija; depressed patients; družinska medicina; general practitioner; kvaliteta dela; podiplomsko izobraževanje; post - graduate education; quality of work; zdravniki